The Importance Of Cultural Background Knowledge In Efl Classes: The Algerian University Teachers’ Attitudes And Perceptions - Ouchene, Nour El Houda; Baghzou, Sabrina (جامعة الوادي - university of Eloued, 2021)
Abstract This descriptive research aims at investigating the attitudes and perceptions towards the importance of cultural background knowledge among the Algerian English as Foreign Language University teachers. Thus, we hypothesize that the participants would have positive attitudes towards the importance of teaching culture in English as foreign language classes. To this end, the data were collected through a Likert questionnaire with 32 statements based on the agreement option webbed to the participants. Eighty teachers from Khenchela University and other Algerian universities answered the questionnaire. The analysis of data was through the use of SPSS version 25. Results highlights tow major findings: EFL university teachers are aware of the importance of cultural background knowledge in their classroom; and it also reveal that teachers believe that learning culture is essential for effective communication.
Article
Keywords: cultural background knowledge ; English as foreign language ; Algerian university teachers ; attitudes ; perceptions